Rekontruksi Teologi Islam Transformatif: Integrasi Tauhid dan Humanistik-Eksistensial sebagai Kritik Aatas Krisis Epistemologis Teologi Kontemporer - Putri Anugerah Al Adhimi; Putri Dwi Nurwulandari; Nury Nailul Mukarromah; Romi Fasya; Ali Hasan Siswanto (Jurnal Teologi Islam, 2026)
The epistemological crisis in contemporary Islamic theology is marked by a disconnect between the normative-doctrinal dimension and the existential experience of modern humans, causing theology to lose its transformative power in addressing the crises of meaning, alienation, and spiritual disorientation. Although various studies have sought to contextualize theology, most remain trapped in a descriptive-historical approach and have not yet addressed the integration between the transcendental and psychological dimensions of humanity. The research gap lies in the absence of a systematic conceptual formulation for integrating Islam-based theology rooted in tawhid with a humanistic-existential psychological approach, particularly the thought of Carl Rogers, which emphasizes subjective experience, self-awareness, and human actualization. This study aims to formulate a paradigm of transformative Islamic theology through the integration of tawhid as an ontological foundation with a humanistic-existential approach as a framework for subjective experience. The theoretical approach employed is interdisciplinary, combining Islamic theology, existential philosophy, and humanistic psychology. The research method employs a qualitative-conceptual approach with philosophical-critical and hermeneutic analysis of classical and contemporary literature. The main argument of this study is that Islamic theology will only be relevant if reconstructed as a living existential consciousness (living theology), not merely as a normative doctrine. The integration of tawhid and the humanistic approach yields a model of transformative theology capable of bridging the relationship between God and humanity in concrete experience. The scientific contribution of this study lies in the development of a new paradigm of Islamic theology that is integrative, existential, and transformative, while enriching interdisciplinary research in contemporary Islamic studies.